Bond behavior of square CFT using manufactured sand and recycled coarse aggregate. (1st February 2021) - Guan, Minsheng; Wang, Gang; Wang, Ying; Wei, Chunqing; Lai, Zhichao; Du, Hongbiao; Liu, Ziyang
Highlights: Experimentally investigates the bond behavior of MS-RCA-CFT. Conducts 48 bond strength tests on MS-RCA-CFT. Evaluates the influences of four test parameters. Evaluates the applicability of current design codes for MS-RCA-CFT. Abstract: This paper experimentally investigated the bond behavior of concrete-filled square steel tubes using manufactured sand and recycled coarse aggregate (referred to as MS-RCA-CFT). A total of 48 specimens were tested to study the effect of the following parameters: (i) concrete compressive strength, (ii) width-to-thickness ratio, (iii) stone powder content, and (iv) type of sand. The test results indicated that MS-RCA-CFT members had similar bond behavior as conventional CFT members. The bond strength increased with increasing concrete compressive strength and decreasing width-to-thickness ratio. Specimens with a stone powder content of 5% to 10% had the highest bond strength, while a higher stone powder content (15% and 20%) had a negative impact on the bond strength. Specimens with manufactured sand exhibited higher bond strength compared with specimens with natural sand. The bond strength of MS-RCA-CFT tested in this research was compared with the bond strength of conventional CFT from literature. Applicability of several design codes in calculating the bond strength of MS-RCA-CFT members, RCA-CFT members, and conventional CFT members was evaluated. Lastly, an analytical model for the bond-slip curve was also evaluated.